New approach to uniformly quasi circular motion of quasi velocity biharmonic magnetic particles in the Heisenberg space - Körpınar, Talat (Wiley, 2021)
In this paper, we define concept of the uniformly quasi circular motion (UQCM) with biharmonicity condition in the Heisenberg space. That is, we aim to define a new class of UQCM in the three-dimensional Heisenberg space. We further improve an alternative method to find uniformly quasi circular potential electric energy of biharmonic velocity magnetic particles in the Heisenberg space. We also give the relationships between physical and geometrical characterizations of uniformly quasi circular potential electric energy. Finally, we illustrate important figures for uniformly quasi circular potential electric energy with respect to its electric field in the radial direction.
Korpinar, Talat/0000-0003-4000-0892
Keywords: electrical energy; Heisenberg space; magnetic flux density; quasi plasma; uniformly quasi circular motion